Analisis Sistem Taawun Dalam Filantropi Muhammadiyah Di Lazismu Kota Medan - Nurul Afni (Integrasi: Jurnal Studi Islam dan Humaniora, 2023)
The purpose of this research is to find out the application of the Taawun System in Muhammadiyah Philanthropy at Lazismu Medan City, to find out to what extent the implementation of the Taawun System in Muhammadiyah Philanthropy at Lazismu Medan City can increase zakat receipts at Lazismu Medan City, to understand what are the obstacles of Lazismu to increase zakat receipts . This research uses a qualitative approach. The results of the study show that the taawun system in Muhammadiyah philanthropy can be implemented properly. LAZISMU as a Facilitator plays a very important role in helping mustahiq or business actors who experience difficulties in developing their business. The impact of this taawun system is an increase in business income which means that the members of the taawun system program in Muhammadiyah philanthropy are able to expand their business network, and increase income profits and develop the business they run. Supporting and Inhibiting Factors in the implementation of this empowerment program are supported by the potential of human resources that can be developed through productivity-based zakat funds, the Muhammadiyah institution is one of the institutions that has structures at every level both regional, regional, branches and branches, and the participation of mosque, Islamic financial institutions and local government. However, the implementation of this empowerment program still has several obstacles, including not all mustahiq can be directed to productivity because of the culture and mentality that influence it, such as the absence of an entrepreneurial spirit, etc. the meaning of professional amil at LAZISMU who fosters program members from all aspects and processes of the empowerment approach. So that the empowerment and assistance that is carried out is not optimal and is only limited to active communication and limited education.